2021
DOI: 10.1515/med-2021-0277
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative inflammation-based predictors in patients with bladder carcinoma after radical cystectomy

Abstract: Aims Emerging evidence has related inflammation-based biomarkers to numerous carcinomas, including bladder carcinoma (BC). However, the role of inflammatory biomarkers in the prognosis of BC remains inconclusive. This study aimed to compare preoperative plasma fibrinogen (PF) and other inflammatory biomarkers such as the platelet–lymphocyte ratio (PLR), neutrophil–lymphocyte ratio (NLR), lymphocyte–monocyte ratio (LMR), C-reactive protein (CRP) level, and serum albumin level to predict the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…This can help in decision making for follow-up scheduling, administration of adjuvant therapies, and precise individualized treatment for patients [ 26 ]. In another study on prognostic value of preoperative inflammation-based predictors in patients with bladder carcinoma by Gui et al, they reported that high plasma fibrinogen levels are associated with a more aggressive clinical stage and plasma fibrinogen levels may be used to predict survival outcome of patients with bladder carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can help in decision making for follow-up scheduling, administration of adjuvant therapies, and precise individualized treatment for patients [ 26 ]. In another study on prognostic value of preoperative inflammation-based predictors in patients with bladder carcinoma by Gui et al, they reported that high plasma fibrinogen levels are associated with a more aggressive clinical stage and plasma fibrinogen levels may be used to predict survival outcome of patients with bladder carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%